Genetic Insights Into the Link Between Restless Legs Syndrome and Diabetic Nephropathy Risk - Yun Lin; Xiaorui Cai; Haohao Chen; Xiaoling Tang (Brain and Behavior)
ABSTRACT Background Restless legs syndrome (RLS) is a common neuro‐sensory disorder associated with various metabolic diseases, including diabetes mellitus and its complications. Observational studies suggest a potential association between RLS and diabetic complications; however, the causal relationship remains unclear due to confounding factors and reverse causation. This study aims to assess the causal relationship between RLS and diabetes, including its complications, using a bidirectional Mendelian randomization (MR) approach. Methods Genetic instruments derived from the latest genome‐wide association study (GWAS) data for RLS, Type 1 diabetes, Type 2 diabetes, and diabetic complications (diabetic nephropathy, diabetic retinopathy, and diabetic neuropathy) were selected on the basis of MR assumptions. For causal inference, RLS was used as the exposure, whereas diabetes and its complications were considered outcomes. Reverse MR analyses were performed to assess potential causal effects of diabetes and its complications on RLS. Primary analysis used the inverse‐variance weighted (IVW) method, with IVW radial and robust adjusted profile score (RAPS) as supplementary methods. Heterogeneity, pleiotropy, and robustness were assessed in both discovery (UK Biobank) and validation (FinnGen) datasets. Results Forward MR analysis revealed a significant causal effect of RLS on the risk of diabetic nephropathy in both the discovery (IVW: OR = 1.049, p = 0.0238) and validation cohorts (IVW: OR = 1.067, p = 0.0028). However, no significant causal relationships were found for other primary outcomes, including Type 2 diabetes (IVW: OR = 1.011, 95% CI: 0.994–1.029) and Type 1 diabetes (IVW: OR = 0.995, 95% CI: 0.967–1.023). Sensitivity analyses showed no evidence of heterogeneity or horizontal pleiotropy. Reverse MR analysis did not demonstrate a causal effect of diabetes or its complications on RLS. Conclusions The findings suggest that RLS causally increases the risk of diabetic nephropathy. Early recognition and management of RLS in patients with diabetes may help prevent or delay the progression of nephropathy. Further studies are warranted to explore underlying mechanisms and potential clinical interventions.